The Power of the Agile Business Analyst, second edition - 30 surprising ways a business analyst can add value to your Agile development team - Cooke, Jamie (IT Governance Publishing, 2018)
Now in its second edition, The Power of the Agile Business Analyst has expanded to include new Agile methods that have emerged or gained prominence since the first edition. Buy this book to learn how to revolutionise your Agile development and increase the value and relevancy of your project outcomes. Learn 30 realistic, achievable ways that an Agile business analyst can increase project efficiency, add value and improve quality. Find out how an Agile business analyst bridges the gap between the needs of the business and the resources of the development team. Now updated with current Agile methods, to support emerging and established business analysts to adapt to new trends. 30 ways an Agile business analyst can help Drawing on her extensive experience, Jamie proposes a new role for Agile projects: The Agile business analyst. She details 30 achievable ways that such a role will increase relevance, quality and overall business value, and provide business users with crucial support. The Agile business analyst is also a boon to the development team, being a ready source of business knowledge and ensuring that project outcomes align with requirements. This book has been updated to: Incorporate behaviour-driven development into the work that the business analyst does to support interface design; Align the programme management strategies of the Scaled Agile Framework (SAFe) to encourage cross-organisational communication and participation; Include full updates throughout the Qualifications section in 'Getting the Right Agile Business Analyst for Your Team'; and Provide Agile updates, bringing the book back into line with current methods . Support your Agile business user for better project outcomes.